ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI WAJIB PAJAK ORANG PRIBADI DALAM MEMENUHI KEWAJIBAN MEMBAYAR PAJAK (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Semarang Candisari) - Fikriningrum, Winda Kurnia; Syafruddin, Muchamad (Diponegoro Journal of Accounting, 2012)
This research aims to analyze the factors that affect individual taxpayers in meeting their to pay taxes obligation. This research consists of four independent variables and one dependent variable. Independent variables in this research is the awareness of tax paying, knowledge and understanding of taxation laws, a good perception of the effectiveness of the tax system and the service of fiscus. While the dependent variable in this research is the willingness to pay taxes. This research uses incidental sampling technique and survey methods with questionnaires and interviews in data collection. Respondents of were sampled in this study is an individual taxpayer who is listed in the Tax Office Primary Semarang Candisari classified as taxpayer effectively. Analysis of research data using multiple linear analysis with SPSS 16.0 program. Based on the results of the analysis has been done, this research shows that awareness of tax paying, knowledge and understanding of taxation laws, a good perception of the effectiveness of the tax system, and the service of fiscus have a positive and significant impact on willingness to pay taxes.